Explaining catch efficiency of cod pots using in situ behavioural studies - Hedgärde, Maria (SLU/Dept. Of Aquatic Resources, 2016)
The seal populations in the Baltic have been growing since the 1980s causing great eco-nomic losses for the fisheries since seals are using fishing gear as easy food sources. One solution to the seal and fishery conflict is the development of seal safe fishing gear. Pots are a possible solution in the cod (Gadus morhua) fishery. The success of pots depends on knowledge of the target species’ behaviour in relation to the gear. There are few previous studies of cod pots relating behaviour of cod to catches of pots by filming the whole catch process. This thesis aimed to investigate how the behaviour of cod affects the catch per unit ef-fort (CPUE) of cod pots. Camera systems were used to record in situ behaviour of cod. The relationship between entries, exits and soak time was studied and predictors explaining entry rate were identified. Fishing trials were conducted of the east coast of Bornholm, Denmark. Video analysis showed continuous entry and exit behaviour of cod during the soak time of a pot. A GAMM analysis was used to identify the predictors explaining CPUE and entry rate. Pot type was one important predictor and most fish entered large, round, bottom standing pots. When artificial light was used in pots, more fish were entering during night time than during the day, the artificial light being a possible explanation for this behaviour. When no light was used the entry rate decreased with soak time, possibly due to the bait loosing odour with time.